University students’ media use and political participation in South Africa - Badaru, K.A.; Adu, E.O. (South African Journal of Higher Education, 2020)
The survival of democracy depends on the active participation of citizens in the political processes. South Africa’s nascent democracy is at risk as long as her young citizens continue to show apathy towards participation in politics. This perceived paucity of youth participation in politics can be reversed through the mass media’s provision of political education. This study, therefore, investigated the influence of media use on university students’ political participation in South Africa. This study adopted a mixed methods design. Questionnaires were administered to 372 students selected, using the stratified random sampling techniques, from one university in the Eastern Cape Province. Semi-structured interviews were conducted among five purposively selected members of the Student Representative Council. Simple descriptive and Pearson correlation statistics were used to analyze the quantitative data while thematic content analysis was performed on the qualitative data. Of the 372 participants, 243 (65.3%), 124 (33.3%), 160 (43.0%), 81 (21.8%) reported the use of the internet, newspaper, television, and radio respectively for political information on a daily basis. A total of 183 (49.2%) and 113 (30.4%) voted in the SRC and national elections respectively. The bivariate analysis reveals that mass media exposure is significantly associated with students’ participation in politics (P<0.001). In conclusion, it is established that there is a strong and positive relationship between students’ mass media use and their participation in politics. It is, therefore, recommended that political education through the mass media would be significantly required to improve students’ interest and participation in politics. The potential advantage of the media especially the social media must be tapped by the university authorities, political organizations and other concerned agencies of government to increase university students’ political knowledge, interest and participation in South Africa.